De novo thyroid cancer following solid organ transplantation—A 25‐year experience at a high‐volume institution with a review of the literature. Issue 2 (5th January 2017) - Kluijfhout, Wouter P.; Drake, Frederick T.; Pasternak, Jesse D.; Beninato, Toni; Mitmaker, Elliot J.; Gosnell, Jessica E.; Shen, Wen T.; Suh, Insoo; Freise, Chris E.; Duh, Quan‐Yang
Abstract : Background and Objectives: We investigated the rate, stage, and prognosis of thyroid cancer in patients after solid‐organ transplantations, and compared this to the general population. Methods: We performed a retrospective review of patients who developed thyroid cancer after a solid‐organ transplantation between January 1988 and December 2013 at a high volume transplant center. Standardized Incidence Ratio's (SIR) were calculated. Additionally, a systematic review of the literature was performed. Results: A total of 10, 428 patients underwent solid organ transplantation. Eleven patients (11.4 per 100, 000 person‐years) developed thyroid cancer: six men and five women with a mean age at diagnosis of thyroid cancer of 58 years. Ten patients underwent surgery and had stage I thyroid cancer. One patient had recurrent disease after a mean follow‐up time of 78 months. The SIR varied between 0.75 and 2.3. Seventeen studies were included in the systematic review with a SIR ranging from 2.5 to 35. Conclusion: Rate of thyroid cancer is not significantly higher in patients who underwent solid organ transplantation compared to general population. Stage at presentation and prognosis also appear to be similar to that of the general population. Post‐transplant screening for thyroid cancer remains debatable; however, when thyroid cancer is discovered, treatment should be similar to that of non‐transplant patients. J. Surg. Oncol. 2017;115:105–108 . © 2017 Wiley Periodicals, Inc.